2007
DOI: 10.1111/j.1471-4159.2007.04998.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glutamate intake during gestation on adenosine A1 receptor/adenylyl cyclase pathway in both maternal and fetal rat brain

Abstract: Pregnant Wistar rats were orally treated with 1 g/L l‐glutamate during the entire gestational period and the status of adenosine A1 receptor (A1R)/adenylyl cyclase transduction pathway from maternal and fetal brain was analyzed. Glutamate consumption, estimated from the loss of water from the drinking bottles, was 110 ± 4.6 mg/kg/day. In mother brains glutamate intake did not significantly alter the Bmax value, although the Kd value was significantly decreased. However in fetus brain, a significant decrease in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…However, in this case, we observed a significant decrease of mGlu 1 and mGlu 5 receptors and a corresponding desensitization of mGlu receptor/PLC signalling pathway [35] which suggest that crosstalk processes may be influenced by different parameters such as gender or routes of administration. In reciprocal experiments, continuous L-glutamate intake throughout gestation also decreased A 1 receptor/AC signalling pathway in the maternal brain [36]. Finally, we have observed not only changes in group I-mGlu receptors functionality upon prolonged exposure to A 1 receptor agonist but also we showed a loss of group I-mGlu receptors responsiveness following chronic caffeine exposure which suggests that the blockade of adenosine receptors might also alter mGlu receptor functionality [37].…”
Section: Functional Interaction Between Adenosine and Mglu Receptorsmentioning
confidence: 80%
“…However, in this case, we observed a significant decrease of mGlu 1 and mGlu 5 receptors and a corresponding desensitization of mGlu receptor/PLC signalling pathway [35] which suggest that crosstalk processes may be influenced by different parameters such as gender or routes of administration. In reciprocal experiments, continuous L-glutamate intake throughout gestation also decreased A 1 receptor/AC signalling pathway in the maternal brain [36]. Finally, we have observed not only changes in group I-mGlu receptors functionality upon prolonged exposure to A 1 receptor agonist but also we showed a loss of group I-mGlu receptors responsiveness following chronic caffeine exposure which suggests that the blockade of adenosine receptors might also alter mGlu receptor functionality [37].…”
Section: Functional Interaction Between Adenosine and Mglu Receptorsmentioning
confidence: 80%
“…Glutamic acid hydrochloride was administered at 2 and 4 g/kg bw as a 20% (w/v) solution and sucrose (in 80% w/v) was given at dosages equimolar to 4, 8 or 10 g MSG/kg bw. Oedema and pyknotic nuclei were seen in sodium chloride-treated animals of 5 days of age; no lesions were seen in animals older than 6 days at the time of treatment, nor in mice given sucrose' (Lemkey-Johnston et al, 1975as referred to by JECFA, 1988.…”
Section: Micementioning
confidence: 95%
“…In another study, pregnant Wistar rats (not further specified) were given L-glutamate at a concentration of 0 or 1,000 mg/L (equal to 0 or 110 mg/kg bw per day) in the drinking water from gestational day 2 and during the whole gestational period (Le on et al, 2008). Brains of both mothers and their offspring were then isolated.…”
Section: Ratsmentioning
confidence: 99%
“…Leon et al suggested that glutamate administered to pregnant rats modulates adenosine A1 receptor signaling pathways in both maternal and fetal brain, showing an adenosine A1 receptor down-regulation in fetal brain, and desensitization in maternal brain. 32 MSG in high doses caused neuronal necrosis in hypothalamic arcuate nuclei in neonatal rats. 33 MSG (4 mg/g.…”
Section: Discussionmentioning
confidence: 91%